A Load Balancing Policy for Distributed Web Service - Eludiora, Safiriyu; Abiona, Olatunde; Aderounmu, Ganiyu; Oluwatope, Ayodeji; Onime, Clement; Kehinde, Lawrence (International Journal of Communications, Network and System Sciences, 2023)
International Journal of Communications, Network and System Sciences, Vol. 3, p.645-654.